Peningkatan Keaktifan dan Hasil Belajar Siswa Melalui Penerapan Aplikasi Canva pada Materi Pembuatan Poster di MTs Negeri 1 Yogyakarta - Dewi Widowati, Rr. Ayu (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to improve student activeness and learning outcomes in learning Cultural Arts poster making materials. This research using the Classroom Action Research (PTK) method was carried out in 2 cycles. The subjects of the study were students in class VIII-C MTs Negeri 1 Yogyakarta. Data is obtained from teachers (observers) and students through observation, tests, and documentation. The results showed that student activeness and learning outcomes in the learning process through the application of the Canva application have increased significantly. In the first cycle, an average class score of 81.06 was obtained with classical learning completeness of 83.87 with the category of students being quite active. In cycle II, the average grade score increased to 87.71 with classical learning completeness reaching 100% with the active student category. The application of the Canva application in learning Cultural Arts poster making materials can increase student activeness and learning outcomes.